Implementasi Platform Match Making sebagai Strategi Pemberdayaan UMKM Ekonomi Kreatif Kota Malang - Saputra, Pramana Yoga; Syaifudin, Yan Watequlis; Mundzir, Hudriyah; Fatmawati, Triana (Universitas Merdeka Malang, 2024)
Creative Economy SMEs (Small and Medium Enterprises) Indonesia, as part of micro, small, and medium enterprises, play a vital role in the national economy with their creative and innovative value addition. This sector encompasses 17 subsectors, including culinary, film, and applications. Malang City, recognized as one of Indonesia's creative cities, exhibited significant growth with 12,345 creative economy MSMEs in 2022, a 10.5% increase from the previous year. The three dominant subsectors are culinary, applications and games, and film, video, and animation. However, MSMEs in Malang face challenges such as lack of capital, low product quality, unappealing packaging, and difficulty in reaching markets. To address these issues, an innovative collaboration platform has been developed, connecting MSMEs with communities, investors, academics, and the government. Through these efforts, MSMEs are expected to enhance competitiveness, product quality, and market access, supporting sustainable growth in the creative economy sector.